Eksperimentasi Teknik Quick On The Draw pada Pembelajaran Matematika Peserta Didik Kelas VIII SMPN 1 Ranah Batahan Kabupaten Pasaman Barat - Yulia, Yulia; Arief, Asmaiwaty; Nora, Apria (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The purpose of this study is to determine the understanding on mathematic concept who were taught by using Quick On The Draw Technique was better than the students who were taught by using conventional technique at Class VIII SMPN 1 Ranah Batahan Kabupaten Pasaman Barat. Quasi experimental that designed randomized control group only design. The population of this research was class VIII students of SMP N 1 Ranah Batahan Kabupaten Pasaman Barat of 4 class. For determine the experimental class and the control class is done by randomly. Classes are chosen as experimental class is a class experiment is VIII.2 class and control class is the class VIII.3. The hypothesis of this study is understanding on mathematic concept who were taught using Quick On The Draw Technique was better that the students who were taught using conventional technique at class VIII of SMPN 1 Ranah Batahan Kabupaten Pasaman Barat. Based on the result of final test students’ understanding on mathematic concept in experiment class was higher than the control class. It can be seen from the mean score of experiment class 70.89,control class was 57.78.Hypothesis testing by using t-test showed that t-was higher than t-hitung>t-tabel (1.97 > 1.68) with degree of freedom 95% so hypothesis is accepted. In conclusion, students’ understanding on mathematic concept who were taught by using Quick On The Draw technique was higher than the students who were taught by using conventional technique at calss VIII of SMPN 1 Ranah Batahan Kabupaten Pasaman Barat. Based on the above description the researcher gives advice to mathematical educator, to make quick on the draw technique as one of alternative to improve understanding of mathematical concepts of learners.Keyword : Quick on The Draw Technique, Understanding on Mathematic Concept